Potensi Kayu Rakyat Pada Kebun Campuran Di Desa Pesawaran Indah Kabupaten Pesawaran - Susni Herwanti (Jurnal Sylva Lestari, 2015)
Nowadays, the demanding of wood is increased as the population grows while the amount of wood from state forest is decreased. Therefore, the state forest can no longer be relied upon as a supplier of wood for the community. At present, the wood supply is fulfilled by the folk wood as the biggest wood supplier in Indonesia. As one of wood supplier in Lampung Province, the potential of folk wood in mix garden of Pesawaran Indah is unknown. Therefore the objectives of this research are to identify the type of wood, the benefit and also to analyze the potential of folk wood in folk's mix garden. The research was conducted for two months from June until July 2011. The sample taken using purposive sampling methode which was from two types of sample: respondent and plot sample. The primary and the secondary data were analyzed qualitatively and quantitatively. The results showed that there are 17 types of wooden folk, namely teak (Tectona grandis), medang (Litsea odorifera), chrysolite (Michelia champaka), hibiscus (Hibiscus macrophyllus), tangkil (Gnetum gnemon), Nutmeg (Myristica fragrant), petai (Leucaena leucochepala), julang jaling (Archidendron microcarpum), hazelnut (Aleurites moluccana), bayur (Pterospermum javanicum), coconut (Cocos nucifera), avocado (Persea americana), dadap (Erythrina sp.), mindi (Melia azedarach), cinnamon (Cinnamomum, spp.), durian (Durio zibethinus) and kedondong (Spondias dulcis). Those timbers were used as carpentry, light construction and firewood. The potential of the folk's wood in the village based on classification of young plants are 28 stems per hectare while the potential based on the classification tree is 156.6 m3 per hectare. Keywords: the folk wood, wood potential, Pesawaran Indah Village, mix garden